(untitled) (Dhaka University Journal of Biological Sciences, 2023)
The study was conducted to identify the protozoan parasites in a freshwater indigenous air breathing fish, Heteropneustes fossilis (Bloch, 1794). The host fish was collected during mid of the April 2018 to end of the March 2019 from freshwater bodies of Mymensingh, Kishoregonj, Faridpur, Jashore, Manikganj and Bogura districts of Bangladesh. Three species of phylum myxozoa namely Henneguya singhi, Henneguya qadrii, Henneguya mystusia, one species of phylum ciliophora namely Trichodina siddiquae and two species of phylum mastigophora namely Trypanosoma singhii and Piscinoodium pillulare were identified in H. fossilis. The parasites of all infected hostswere observed in gill, body slime and blood, however gillswere commonly infected by parasites rather than body slime and blood. Three species of parasite Piscinoodium pillulare, Henneguya qadrii and Henneguya mystusia were first recorded in this host fish and novel locality record in Bangladesh. H. fossilis was found to be infected over the three major (p<0.05) (summer, rainy and winter) seasons and demonstrated a strong significant association (P0<05) with season during the study period. In H. fossilis, highest variety and highest number of parasites were found in winter season, prevalence and intensity was found 78.31% and 5.17 respectively. Lowest prevalence and intensity were found in rainy season respectively 45.87 and 4.72. Among all the parasites Henneguya singhi was common in all the three seasons and its rate of infection was found elevated in summer (20.69%) and rainy season (19.27%). In H. fossilis prevalence of female fish were highest in all the three seasons, summer (55.22%), rainy (50.75%) and winter (85.57%) than their male counterparts 38.76%, 38.09% and 68.12%, respectively. Dhaka Univ. J. Biol. Sci. 32(1): 21-32, 2023 (January)